2004
DOI: 10.1083/jcb.200406073
|View full text |Cite
|
Sign up to set email alerts
|

Decreased apoptosome activity with neuronal differentiation sets the threshold for strict IAP regulation of apoptosis

Abstract: Despite the potential of the inhibitor of apoptosis proteins (IAPs) to block cytochrome c–dependent caspase activation, the critical function of IAPs in regulating mammalian apoptosis remains unclear. We report that the ability of endogenous IAPs to effectively regulate caspase activation depends on the differentiation state of the cell. Despite being expressed at equivalent levels, endogenous IAPs afforded no protection against cytochrome c–induced apoptosis in naïve pheochromocytoma (PC12) cells, but were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 53 publications
2
92
0
Order By: Relevance
“…Importantly, because MOMP often kills irrespective of caspase activity, it is considered a cellular death sentence 12 . Nevertheless, there are notable exceptions; for example some types of neurons can circumvent the lethal effect of MOMP by inhibiting caspase activity through various means including low expression of APAF-1 or degradation of cytochrome c 13,14 . Moreover, proliferating cells under caspase-inhibited conditions can also survive MOMP dependent upon glycolytic metabolism and autophagy 15 .…”
Section: Apoptotic Signaling Pathwaysmentioning
confidence: 99%
“…Importantly, because MOMP often kills irrespective of caspase activity, it is considered a cellular death sentence 12 . Nevertheless, there are notable exceptions; for example some types of neurons can circumvent the lethal effect of MOMP by inhibiting caspase activity through various means including low expression of APAF-1 or degradation of cytochrome c 13,14 . Moreover, proliferating cells under caspase-inhibited conditions can also survive MOMP dependent upon glycolytic metabolism and autophagy 15 .…”
Section: Apoptotic Signaling Pathwaysmentioning
confidence: 99%
“…For example, in many mitotic cells such as HeLa cells, HEK 293 cells, primary fibroblasts and naïve PC12 cells, the addition of cytochrome c to cytosolic extracts or injection of cytochrome c into the cytosol of these cells induces rapid caspase activation and apoptosis. [4][5][6][7][8] In contrast, cytochrome c, although necessary, is not sufficient to induce apoptosis in postmitotic cells such as sympathetic neurons, differentiated PC12 cells and cardiomyocytes. 2,5,9,10 Recently, the X-linked inhibitor of apoptosis protein (XIAP) was identified as the critical regulator of caspase activation in these postmitotic cells.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] In contrast, cytochrome c, although necessary, is not sufficient to induce apoptosis in postmitotic cells such as sympathetic neurons, differentiated PC12 cells and cardiomyocytes. 2,5,9,10 Recently, the X-linked inhibitor of apoptosis protein (XIAP) was identified as the critical regulator of caspase activation in these postmitotic cells. 9,11 XIAP is a member of a family of inhibitor of apoptosis proteins (IAPs) that have been shown to regulate caspases by directly binding to and inhibiting their function.…”
mentioning
confidence: 99%
“…Levels of Apaf-1 in sympathetic neurons were significantly decreased in comparison to the other cell types, consistent with our previous observations indicating that postmitotic sympathetic neurons contain low levels of Apaf-1. 29 Strikingly, in comparison to dermal fibroblasts and cortical neurons which express a significant amount of procaspase-7, sympathetic neurons expressed virtually undetectable levels of procaspase-7 protein (Figure 4). We also examined caspase-7 expression by semiquantitative PCR and found that caspase-7 mRNA transcripts in sympathetic neurons were markedly reduced in comparison to cortical neurons (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 94%
“…First, by having reduced levels of Apaf-1, sympathetic neurons engage a strict regulation of caspase activation by endogenous XIAP. 29 Second, these neurons have the unique capacity to recover when the apoptotic pathway is arrested even after cytochrome c release. Third, the lack of significant caspase-7 expression in sympathetic neurons results in a non-redundant pathway that is dependent on caspase-3 alone for effector caspase function.…”
Section: Discussionmentioning
confidence: 99%